2000
DOI: 10.1155/s106474490000034x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus, Chlamydia trachomatis, and Neisseria gonorrhoeae in CommercialSex Workers in Japan

Abstract: The high prevalence of HPV, C. trachomatis, and N. gonorrhoeae infection in CSW poses a risk of further transmission of STD to the general public, suggesting the need for further education and screening for CSW and the general public. We found high- and intermediate-oncogenic-type HPV to be the most prevalent infection among both CSW and control subjects. Screening for HPV may be necessary in STD and general clinics to predict the risk of cervical malignancy. Hybrid capture assays, which permit simultaneous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 8 publications
3
21
1
2
Order By: Relevance
“…Nonetheless, in our study we did not find any case of genital infection by N. gonorrhoeae, although capture assays permit simultaneous detection of HPV and other STD with high sensitivity [23].…”
Section: Discussioncontrasting
confidence: 70%
“…Nonetheless, in our study we did not find any case of genital infection by N. gonorrhoeae, although capture assays permit simultaneous detection of HPV and other STD with high sensitivity [23].…”
Section: Discussioncontrasting
confidence: 70%
“…Our detection rate of HPV in commercial sex workers (47%) was higher than the 14.8% of Molano et al [2002], 28.7% of Figueroa et al [1995], and 30.6% of Chan et al [2002] but was similar with 48.4% of Ishi et al [2000]. Some studies have reported that more than one genital HPV genotype is found in >50% of sexually active adults as a common sexually transmitted disease (STD) [Koutsky, 1997].…”
Section: Discussionmentioning
confidence: 44%
“…Studies from both the developed and developing countries have confirmed this, which suggests that sex workers should have more frequent Pap smears. [8][9][10][11] It is also known that the disparity between the HPV infection rates in sex workers and the general population varies considerably depending on the country. In Japan, the prevalence of high-risk HPV infection in female sex workers as detected by DNA methodology was 48%, as compared with only 6% in the general population, 11 while in Australia, there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%